Pemodelan Data Panel dengan Pendekatan Least Square Dummy Variable terhadap Faktor-Faktor yang Memengaruhi Kasus Kriminalitas di Sulawesi Selatan - Nurdin, Afifah Mutiah; Arfan, Muh. Indirwan; Siswanto, Siswanto; Kalondeng, Anisa (Hasanuddin University, 2024)
Crime is one of the challenges that often arises in the community environment. In the years 2020-2022, South Sulawesi ranked fourth with the highest reported crime cases in Indonesia. To avoid an increase in the crime rate, an understanding of the factors impacting these cases is necessary. This research aims to determine the fixed effect model with the Least Square Dummy Variable approach to examine the percentage of the poor population, income inequality, population density, and the total population's influence on crime cases in South Sulawesi during the years 2020-2022. The most suitable model is the Least Square Dummy Variable using an individual effect with an analysis result of of 99.9%. The variables of the percentage of the poor population, population density, and the total population are proven to significantly influence crime cases in South Sulawesi.